2022
DOI: 10.2118/208613-pa
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Prediction of Proppant Placement along a Horizontal Fracturing Stage for Perforation Design Optimization

Abstract: Summary Multistage plug and perforation (plug-n-perf) fracturing is commonly used for horizontal well completion in unconventional reservoirs. Uniform distribution of proppant across all clusters in each stage has proved to be challenging with low viscosity slickwater owing to its limited transport capability. Computational fluid dynamics (CFD) has been used to model proppant transport in wellbore to improve perforation and fracturing design for achieving uniform proppant placement. However, tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The displacement of the latter slip is denoted by s. Note that the fact that proppant located only near the perforation leaves the wellbore was observed in [19] via CFD simulations and the area outlined by l p was called the "ingestion area". Similarly, authors in [18] plotted the fluid and proppant streamlines, which confirmed that the "ingestion" area is nearly circular and that there is a difference between those areas for fluid and proppant, as outlined by l f and l p . Fig.…”
Section: Proppant Turning From Wellbore To a Perforationmentioning
confidence: 55%
See 4 more Smart Citations
“…The displacement of the latter slip is denoted by s. Note that the fact that proppant located only near the perforation leaves the wellbore was observed in [19] via CFD simulations and the area outlined by l p was called the "ingestion area". Similarly, authors in [18] plotted the fluid and proppant streamlines, which confirmed that the "ingestion" area is nearly circular and that there is a difference between those areas for fluid and proppant, as outlined by l f and l p . Fig.…”
Section: Proppant Turning From Wellbore To a Perforationmentioning
confidence: 55%
“…While the system of equations (18) gives the complete or full model, it requires solving a two-dimensional equation, which needs significantly more computational effort than classical wellbore simulation approaches. Therefore, the purpose of this section is to outline a reduced model, that is based on the steady-state solution (19), but yet still captures the dominant effect of time dependence.…”
Section: Reduced Modelmentioning
confidence: 99%
See 3 more Smart Citations